Biostratigraphy and sedimentology of the Ionian Zone Ammonitico Rosso in the Mavron Oros area (NW Epirus, Greece) - Paleogeographic implications. - Karakitsios, V.; Chatzicharalampous, E. (Bulletin of the Geological Society of Greece, 2013)
New biostratigraphic and sedimentologic data on the Ammonitico Rosso (AR) formation in the Mavron Oros area (Ionian zone, NW Epirus) show that its thickness progressively reduces towards the N-NW (from 15 to 7m). Two sections were studied, in the thick (A) and thin succession (B) respectively. The ammonite fauna indicates a stratigraphic range for the AR from the early Toarcian to the Aalenian, in section A, and from the upper part of Middle Toarcian to the Aalenian, in section B. Thus, AR deposition was transgressive, confirming the stratigraphic pinching-out of the synrift formations, observed in the same area towards the N-NW. Sedimentologic observations showed that the AR in section B (where AR base is missing) consists of nodular mud-to wackestones with subsolved ammonite shells, and clear indices of early lithification and subsequent solution of fine carbonate material. These observations indicate low rates of sedimentation and repeated phases of non-deposition and submarine erosion, characteristic for seamount environment.